2001
DOI: 10.1128/iai.69.1.288-296.2001
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Human Immune Response byEchinococcus granulosusAntigen B and Its Possible Role in Evading Host Defenses

Abstract: ). AgB skewed the Th1/Th2 cytokine ratios towards a preferentially immunopathology-associated Th2 polarization, predominantly in patients with progressive disease. AgB-stimulated patients' PBMC also proliferated less than SHF-stimulated PBMC (P ‫؍‬ 9 ؋ 10 ؊3 ). In vitro Th2 cytokine production was reflected in vivo by elevated specific immunoglobulin E (IgE) and IgG4 antibodies binding to AgB. These findings confirm that AgB plays a role in the escape from early immunity by inhibiting PMN chemotaxis. They also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
117
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(124 citation statements)
references
References 37 publications
4
117
0
3
Order By: Relevance
“…About 10% of the hydatid fluid protein fraction is composed by a polymeric thermo-stable lipoprotein (Musiani et al, 1978), the antigen B (AgB), whose role in the immune response evasion is suggested by several lines of evidence. First, the antigen inhibits neutrophil chemotaxis and elastases in vitro (Shepherd et al, 1991); second, it elicits a non-protective Th2 immune response (Riganú et al, 2001); and, finally, it induces immune cell apopoptosis in patients with hydatid disease (Riganú et al, 2002). The native antigen, built by subunits of 8 kDa, is highly immunoreactive.…”
Section: Introductionmentioning
confidence: 99%
“…About 10% of the hydatid fluid protein fraction is composed by a polymeric thermo-stable lipoprotein (Musiani et al, 1978), the antigen B (AgB), whose role in the immune response evasion is suggested by several lines of evidence. First, the antigen inhibits neutrophil chemotaxis and elastases in vitro (Shepherd et al, 1991); second, it elicits a non-protective Th2 immune response (Riganú et al, 2001); and, finally, it induces immune cell apopoptosis in patients with hydatid disease (Riganú et al, 2002). The native antigen, built by subunits of 8 kDa, is highly immunoreactive.…”
Section: Introductionmentioning
confidence: 99%
“…The antigen is present in large amounts in the metacestode cyst fluid, and its biological functions suggest that it may play a relevant role in the host/parasite interaction. AgB has been reported as a protease inhibitor that impairs the recruitment of polymorphonuclear cells and skews the Th1/Th2 cytokine ratio toward an immunopathology-associated Th2 polarization (4,5). In human infections, AgB is highly immunogenic, which has prompted its use as a diagnostic reagent.…”
mentioning
confidence: 99%
“…Most studies on CE cytokines are mainly based on in vitro experiments, determination of cytokine production following stimulation of peripheral blood mononuclear cell or T helper cells of patients and healthy with crude and B antigens [20,6]. These studies demonstrated an increasing in the production of some cytokines such as IFN-γ, IL-4, and IL-5.…”
Section: Discussionmentioning
confidence: 99%
“…AgB can be measured in patient blood as circulating antigen [4], and it has been suggested that it plays an important role in the biology of the parasite and its relationship with the host [5,6].AgB is a highly immunogenic molecule, a characteristic that underpins its value in serodiagnosis . It appears ladder-like under reduced condition on SDS-PAGE, with three bands with molecular sizes of approximately 8 or 12, 16, and 24 kDa, suggesting that it comprises polymers of 8-kDa subunits [7].The smallest subunit has proved the most useful target in diagnostic studies [8].Observing that the 12-kDa subunit of AgB is a protease inhibitor with the ability to inhibit neutrophil recruitment.…”
Section: Introductionmentioning
confidence: 99%